2012
DOI: 10.1530/eje-12-0111
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations in the frequency of thyroid disorders and thyroid peroxidase antibodies in persons without former thyroid disease within Germany

Abstract: Objective: To investigate regional variations in the frequency of undiagnosed thyroid disorders among 25-to 88-year-old men and women in two communities in the northeast and the south of Germany. In addition, autoantibodies to thyroperoxidase (TPO-Abs) and urinary iodine excretion were determined. Methods: Two population-based surveys of men and women using a common standardized protocol, the Study of Health in Pomerania (SHIP) in the northeast of Germany (2505 participants) and the Kooperative Gesundheitsfors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
3
34
0
8
Order By: Relevance
“…Thus, there might be differences in iodine supply across the regions of Germany (23). However, our new established reference range for serum TSH levels showed good agreement with recent reference ranges established in East (7) and South Germany (35).…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, there might be differences in iodine supply across the regions of Germany (23). However, our new established reference range for serum TSH levels showed good agreement with recent reference ranges established in East (7) and South Germany (35).…”
Section: European Journal Of Endocrinologysupporting
confidence: 78%
“…After the persistence of improved iodine supply for several years, it can be expected that the TSH distribution in the general population shifts toward the right, which has already been observed in Germany (23,24). Thus, the TSH reference interval established during the transition phase between iodine deficiency and sufficiency may not reflect the current distribution of TSH values in the general population of Germany, which might result in unnecessary clinical work-up and high costs for the German health care system.…”
Section: Introductionmentioning
confidence: 99%
“…However, the iodine:creatinine ratio was negatively associated with FT 4 and rT 3 in our study. Studies longitudinally evaluating subjects after iodine fortification have shown a rather surprising positive association between urinary iodine excretion and TSH levels (34,50). In iodine-sufficient populations, findings suggest a positive linear relation between iodine levels and TSH (36), whereas in subjects with urinary iodine excretion below 50 mg/24 h (moderate iodine deficiency), a negative correlation between urinary iodine and TSH was observed (55).…”
Section: Pz009mentioning
confidence: 99%
“…Notwithstanding the rather narrow age range in our study population, we observe inverse associations between increasing age and TSH as well as THs. Previous studies on this topic have not been straightforward: both an increase as well as a decrease in TSH with progressing age has been observed (29,30,34,50). Differences in iodine status of a population might be an explanation for this paradox as well as the thoroughness of exclusion of subjects with thyroid auto-immunity.…”
Section: Pz009mentioning
confidence: 99%
“…As with the whole of Germany, the region was formerly iodine deficient until the mid1990s, when an iodine fortification program became effective (17). Particularly among older persons, goiter prevalence is still high (18).…”
Section: Study Populationmentioning
confidence: 99%